Flickan ritar sig fri: Det naiva barnperspektivet i den postmoderna bilderboken - Österlund, Mia (Tidskrift för litteraturvetenskap, 2009)
The Girl Draws Her Way to Freedom. The Naïve Perspective of the Child in the Postmodern Picture book. This article considers ideological aspects of postmodern Swedish picture books, with particular emphasis on the ways in which picture books construct girlhood in terms of agency. Analysing Finn Zetterholm’s and Mimmi Tollerup-Grkovic’s Klara hela dagen (Klara All Day Long), 2000, and Håkan Jaensson’s and Gunna Grähs’ Rita ensam hemma (Drawing Alone at Home), 2002, the article explores how the motif of drawing is used as a tactic to perform agency for girls in relation to their age. Drawing on insights from feminist poststructuralist research concerned with the textual production of gendered subjectivities, the article considers how a naïve perspective is used as a means to empower girl protagonists by making their subjectivities visible. The two picture books studied here represent two different ways of enhancing the girl protagonists’ agency: the effect tactic and the defusing tactic. The argument proposed is that the motif of the drawing girl in picture books is a modified version of tactics known from girls’ books and young adult fiction, as well as a response to the public debate on strong girls and girl power.